2022
DOI: 10.1002/adpr.202100179
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Loading‐Curve Characteristics of the Persistent Phosphor SrAl2O4:Eu2+,Dy3+,B3+: The Effect of Temperature and Excitation Density

Abstract: The compound SrAl2O4:Eu2+,Dy3+ is currently one of the best‐performing persistent phosphors and numerous studies have been performed to understand the mechanisms involved in its afterglow process. One aspect which so far has received only limited attention is the dependence of loading curve characteristics on dopant concentrations. Herein, a detailed study of the loading curves of SrAl2O4:Eu2+,Dy3+ as a function of composition, sample temperature, and pump intensity is presented, completed by emission decay an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Diaz-Torres and co-workers reported that Sr 4 Al 14 O 25 :Eu 2+ ,Dy 3+ ,Bi 3+ phosphors with different bismuth concentrations always decrease the emission spectra and afterglow time, [204] which can be attributed to the formed quenching centers. In other systems, like ZnGa 2 O 4 :Cr 3+ ,Bi 3+ , [90a] Ca 3 Ga 2 Ge 3 O 12 :Cr 3+ ,Bi 3+ , [172b] Zn(Ga 1-x Al x ) 2 O 4 :Cr 3+ ,Bi 3+ , [181a] ZnGa 2 O 4 :Cr 3+ ,B 3+ , [205] SrAl 2 O 4 : Eu 2+ ,Dy 3+ ,B 3+ , [35,206] Ca 0.85 Zn 0.15 TiO 3 :Pr 3+ ,B 3+ , [152] Ca 2 Zn 4 Ti 16 O 38 : Pr 3+ ,B 3+ , [79] and Sr 4 Al 14 O 25 :Eu 2+ ,Dy 3+ ,B 3+ , [207] a certain extent of PL improvements were present, while the mechanisms are divergent, such as the suppression of the self-reduction effect of Cr 3+ , [90a] formation of the electron traps as the Cr 3+ -Bi 3+ couple, [172b] and probably increased depth or concentration of the traps. [35,205] Obviously, further and deep studies are in urgent need.…”
Section: Design Of Non-rare-earth Co-dopantsmentioning
confidence: 99%
“…Diaz-Torres and co-workers reported that Sr 4 Al 14 O 25 :Eu 2+ ,Dy 3+ ,Bi 3+ phosphors with different bismuth concentrations always decrease the emission spectra and afterglow time, [204] which can be attributed to the formed quenching centers. In other systems, like ZnGa 2 O 4 :Cr 3+ ,Bi 3+ , [90a] Ca 3 Ga 2 Ge 3 O 12 :Cr 3+ ,Bi 3+ , [172b] Zn(Ga 1-x Al x ) 2 O 4 :Cr 3+ ,Bi 3+ , [181a] ZnGa 2 O 4 :Cr 3+ ,B 3+ , [205] SrAl 2 O 4 : Eu 2+ ,Dy 3+ ,B 3+ , [35,206] Ca 0.85 Zn 0.15 TiO 3 :Pr 3+ ,B 3+ , [152] Ca 2 Zn 4 Ti 16 O 38 : Pr 3+ ,B 3+ , [79] and Sr 4 Al 14 O 25 :Eu 2+ ,Dy 3+ ,B 3+ , [207] a certain extent of PL improvements were present, while the mechanisms are divergent, such as the suppression of the self-reduction effect of Cr 3+ , [90a] formation of the electron traps as the Cr 3+ -Bi 3+ couple, [172b] and probably increased depth or concentration of the traps. [35,205] Obviously, further and deep studies are in urgent need.…”
Section: Design Of Non-rare-earth Co-dopantsmentioning
confidence: 99%
“…It is evident that the incorporation of Sn 4+ into the phosphor lattice significantly lowers the QY. The results of the quantum efficiency test demonstrate that the rate of trapping in Sn‐doped phosphors is significantly higher than the rate of radiative emission 29 . The process of determining the QY, using an integrated sphere, is illustrated in Figure S7a–e.…”
Section: Resultsmentioning
confidence: 99%
“…This can also explain why we observe a significant reduction in QY of emission, decreasing from around 21% to 5% because of the presence of Sn 4+ . 29…”
Section: Temperature Dependencementioning
confidence: 99%
“…Thicker transparent crystals (1.5 mm thickness) exhibit more intense afterglow than thinner transparent crystals (0.6 mm thickness) as a larger volume of the sample could be excited in the inner part of the material (see data in Figure 2). This can be expressed as a volume effect [28,29] . Indeed, the initial intensity is about 1.7 times higher for the 1.5 mm crystals in regards to the 0.6 mm crystal.…”
Section: Optical Features Under 455 Nm Excitationmentioning
confidence: 99%